Study On Fishing Technology Of The Scraping Net At Tanjung Pasir Village, Tanah Merah District, Indragiri Hilir Regency, Riau Province - Rengi, Pareng; Brown, Arthur; ', Syarifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A series survey activities was conducted on April 2014 at the Tanjung Pasir Village, Tanah Merah District, Indragiri Hilir Regency, Riau Province. The purpose of this study is to know operation technique, profitability fishing effort, and environmentally of the scraping net which used by fishermen at the Tanjung Pasir Village. The result shows that scraping net is lees be environmentally fishing technology, its based to the 9 creteria of FAO (1995). Based on the profitability analysis show that the Benefit Cost Ratio (BCR) was 1,9, Financial Rate or Raturn (FRR) was 23,2% and Payback Period of Capital (PPC) was 4 months. From the Profitability fishing effort analyzed of scraping net is giving profitable and properly to be continued.keywords :Scraping net, fishing technology, profitability, Tanjung pasir village